Emerging evidence that armed conflict and coca cultivation influence deforestation patterns. (November 2019) - Negret, Pablo Jose; Sonter, Laura; Watson, James E.M.; Possingham, Hugh P.; Jones, Kendall R.; Suarez, Cesar; Ochoa-Quintero, Jose Manuel; Maron, Martine
Abstract: The effect of armed conflict on deforestation in biodiverse regions across Earth remains poorly understood. Its association with factors like illegal crop cultivation can obscure its effect on deforestation patterns. We used Colombia, a global biodiversity hotspot with a complex political history, to explore the association of both armed conflict and coca cultivation with deforestation patterns. We generated spatial predictions of deforestation pressure based on the period 2000–2015 to understand how armed conflict and coca cultivation are associated with spatial patterns of deforestation and assess the spatial distribution of deforestation pressure induced by armed conflict and coca cultivation. Deforestation was positively associated with armed conflict intensity and proximity to illegal coca plantations. A deforestation model including 14 variables was 78% accurate in predicting deforestation at a 10 km 2 resolution. On their own armed conflict and coca cultivation had a notable effect, particularly in the Amazon, but in combination with other variables it was small. Deforestation pressure induced by armed conflict and coca cultivation was highest in Tumaco and Catatumbo regions and in la Macarena, Sierra Nevada and San Lucas mountains—all areas of high biodiversity and conservation importance. In some regions, lack of governance after the peace accords is increasing armed conflict, and our results suggest that those increases in conflict may increase deforestation in those areas. The methods used here can be replicated to help understand the complex ways in which armed conflict affects deforestation patterns in other regions.